Endovascular Thrombectomy >24-hr From Stroke Symptom Onset - Manning, Nathan W.; Wenderoth, Jason; Alsahli, Khalid; Cordato, Dennis; Cappelen-Smith, Cecilia; McDougall, Alan; Zagami, Alessandro S.; Cheung, Andrew (Frontiers in Neurology, 2018)
Background: Trials have demonstrated efficacy for endovascular thrombectomy (EVT) for anterior circulation acute ischaemic stroke (AIS) up to 24-hours from symptom onset. The magnitude of effect suggests benefit may exist beyond 24-hours. Objectives: To perform a retrospective review of all patients undergoing EVT for anterior circulation LVO stroke beyond 24-hours from symptom onset and assess safety and efficacy. Methods: A prospectively maintained database of EVT patients treated at two comprehensive stroke centres between January 2016 and December 2017 was retrospectively screened. Patients undergoing EVT for anterior circulation AIS >24-hours from symptom onset were selected. Results: A total of 429 AIS patient underwent EVT in the study period. Five patients treated >24-hours from symptom onset were identified. The median age was 72 (range 42-84); median ASPECTS 8 (range 6-8); median baseline-NIHSS 9 (range 4-17); and median time from symptom onset to groin puncture 44 hours 55 minutes (range 25:07-90:10). One patient underwent CT perfusion imaging. The remaining four patients were selected based on non-contrast CT brain and CT-angiography. Two patients had tandem cervical carotid lesions and underwent acute stenting. Modified thrombolysis in cerebral ischaemia (mTICI) 3 reperfusion was achieved in four patients. No haemorrhagic transformation occurred. All patients were alive at 90-day follow-up. Four patients achieved functional independence at 90-days (mRS 0-2). Conclusion: Endovascular thrombectomy for AIS patients beyond 24-hours from symptom onset appears to be safe and effective in this limited study. There is a need for further evidence-based trials of benefit versus risk in very prolonged time windows.